Reconfigurable 2.4-/5-GHz dual-band transmitter front-end supporting 1024-QAM for WLAN 802.11ax application in 40-nm CMOS - Liu, Bei (2020)
This article presents a new design methodology of a reconfigurable dual-band output matching network with high efficiency. The implemented output matching network achieves a passive efficiency of 71.6% and 75% at 2.4 and 5.5 GHz, respectively. Based on the proposed output matching network, a transmitter and a standalone power amplifier (PA) supporting 2.4-/5-GHz dual-band operation for the emerging wireless local area network (WLAN) 802.11ax application are designed and fabricated in 40-nm CMOS technology. In 2.4- and 5-GHz, WLAN bands, the PA achieves a Psat of 23 and 21.9–22.4 dBm with power-added efficiency (PAE) of 27% and 24.2%–28.2%,respectively. At 2.442 GHz, the transmitter delivers 8.1-dBm average output power for 40-MHz, 1024-quadrature amplitude modulation (QAM) 802.11ax signal while meeting the standard specification of error vector magnitude (EVM) below − 35 dB. In 5-GHz operating mode, the transmitter achieves an average output power of 6.72-6.95 dBm with the EVM of − 35 dB for 80-MHz, 1024-QAM 802.11ax signal. The PA and transmitter front end are the first published designs for dual-band WLAN 802.11ax application in the literature.